Jazz Cosmopolitanism in Accra : Five Musical Years in Ghana - Feld, Steven (Book collections on Project MUSE., 2012)
Feld combines memoir, biography, ethnography, and history, telling a story of diasporic intimacy and dialogue that contests both American nationalist and Afrocentric narrations of jazz history.